2020
DOI: 10.1093/zoolinnean/zlaa045
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of closely related taxa: the case of the little shearwater complex in the North Atlantic Ocean

Abstract: Seabirds inhabiting vast water masses provide numerous examples where opposing phenomena, such as natal and breeding philopatry vs. vagility have dug cryptic taxonomic boundaries among closely related taxa. The taxonomy of little shearwaters of the North Atlantic Ocean (Little–Audubon’s shearwater complex, Puffinus assimilis–lherminieri) still remains unclear, and complementary information on non-breeding distributions and at-sea behaviour becomes essential to unravel divergent local adaptations to specific ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…Thus, these two species may have hybridized during the Pleistocene. In addition, P. boydi and P. lherminieri show some contemporary overlap in their wintering areas ( Ramos et al 2020 ), which may be a relic of a previously higher overlap in distribution. Future studies should use population genomics data in order to confirm whether the observed patterns are due to ancestral introgression between these two species or to ancestral population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these two species may have hybridized during the Pleistocene. In addition, P. boydi and P. lherminieri show some contemporary overlap in their wintering areas ( Ramos et al 2020 ), which may be a relic of a previously higher overlap in distribution. Future studies should use population genomics data in order to confirm whether the observed patterns are due to ancestral introgression between these two species or to ancestral population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Even foraging ecology, which strongly depends on SST, may be an important process shaping divergence among lineages, as segregation of foraging areas among populations is an important factor of differentiation among seabirds (Friesen, 2015; Friesen et al, 2007), shearwaters (Genovart et al, 2007; Gómez‐Díaz et al, 2006), petrels (Gangloff et al, 2013; Welch et al, 2012), storm‐petrels (Deane, 2013; Smith et al, 2007), and albatrosses (Alderman et al, 2005; Burg & Croxall, 2001). Assessment of nonbreeding and breeding distributions at sea of the little shearwaters complex revealed that all three Atlantic taxa show rather separated foraging and wintering areas (Ramos et al, 2021), and further suggest that boydi rather than lherminieri was ancestral in the North Atlantic. Indeed, boydi is more flexible in its foraging ecological niche, suggesting ancestral behavior (Zajková et al, 2017; see map in Ramos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using this single marker, three distinct lineages were recognized in the North Atlantic: lherminieri in the Caribbean and off Brazil, baroli in the Azores, Canaries, and Madeira, and boydi in Cape Verde (Figure 1). In the North Atlantic, lineages are characterized by nonoverlapping breeding and nonbreeding distributions at sea (Ramos et al, 2021) and are thus geographically separated. Still, they are morphologically and ecologically highly similar (Precheur et al, 2016), a pattern typical of the first stages of the speciation process, the so‐called gray zone (De Queiroz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned species pairs, other shearwater species showed weak patterns of population structure and genetic distances within the interval among different subspecies: P. boydi and P. baroli , and the three Atlantic Calonectris species. These species complexes are the subject of ongoing taxonomic debate (Genovart et al, 2013;Gomez-Diaz et al, 2009;Olson, 2010;Sangster, Collinson, Helbig, Knox, & Parkin, 2005;Ramos et al, 2020). As a final consideration, our genomic data, together with ongoing taxonomic debate, suggest that these taxa should not be granted species status.…”
Section: Considerations Of Shearwater Taxonomymentioning
confidence: 82%
“…Most extant Puffinus species are short-distance migrants or dispersers that remain close to their breeding sites throughout the year (e.g. Ramos et al, 2020). Their lower dispersal compared to other shearwater genera may have reduced gene flow and promoted higher species richness.…”
Section: Biogeographic History Of Shearwatersmentioning
confidence: 99%